THE ISLAMIC FACTOR IN CENTRAL ASIAN COUNTRIES’ DOMESTIC STABILITY - SIDOROV, Oleg (CENTRAL ASIA AND THE CAUCASUS, 2007)
We have to admit that the counterterrorist strategy the world has accepted as the dominant one turned out to be counter-productive in at least two respects: it relies too much on the use of force and mars relations with the Islamic world: The clash of civilizations that so far remains a much-discussed theoretical issue may turn into an unwelcome reality. This fully ap-plies to the Central Asian countries, which, after the Soviet Union’s demise, have been living through a renaissance of certain religious teachings. All sorts of public associations are exhibiting an obvious bias toward religion and the spiritual factor to the extent that the neighboring Soviet successor states and the West developed a deep concern over the spread of so-called Islamic fundamentalism commonly believed to be generated by the Islamic world, which, according to a widespread Western opinion, regards Central Asia as part of its religious territory to be drawn closer and engulfed. Early in the 1990s, the newly independent states experienced an upsurge of national self-awareness inevitably accompanied by a similarly active religious factor. The region was acquiring new mosques and madrasahs at a fast pace and accommodated a flow of Muslim clerics from abroad. This objective process brought the latent threat of Islamic fundamentalism augmented by the closeness of Afghanistan and Iran, as well as by Wahhabi emissaries and organizations that operated on Saudi money.1 The domestic situation, a product of two newly developed problems—the absence of an official ideology and the inefficient efforts of religious organizations to restore stability in the region or, at least, in some countries—was far from simple. During the years of independence, many of the local countries have accomplished much in this sphere: local people an masse are embracing their traditional religions, which is simplifying regional integration.